Willingness and Hesitancy to Vaccinate Against COVID-19 in People with Multiple Sclerosis - Bučaitė, D.; Valinčiūtė, J.; Mickevičienė, D. (Neurologijos seminarai, 2023)
Introduction. During the pandemic, vaccination against COVID-19 has become one of the most important ways to prevent severe infection. However, a lack of trust in vaccines among the population, including people with multiple sclerosis (MS) has been identified. In Lithuania, the specific reasons for vaccine hesitancy among people with MS have not been described. We conducted a survey to determine the attitude of people with MS towards vaccination against COVID-19 infection. Methods. An original anonymous questionnaire was created. The survey included the following aspects: patient demographics, MS exacerbation, COVID-19 vaccination status, and attitudes towards the vaccination process. The survey was conducted between November 2021 and February 2022. Data were analyzed using IBM SPSS Statistics 27.0 with Chi-square and Mann-Whitney U tests and p-value (statistically significant at <0.05) for each hypothesis. Results. Of the 80 MS patients, 82.5% (n=66) were vaccinated and only 17.5% (n=14) were not vaccinated. The most popular positive opinions about vaccination were: “COVID-19 vaccines have more benefits than harm” (71.6%) and “the desire to prevent severe symptoms/hospitalization caused by COVID-19 infection” (79.1%), while mostly agreed negative opinion was “fear of side effects of the vaccine” (84.6%). Intended uptake of COVID-19 vaccines was strongly associated with younger age (p=0.021), higher education level (p=0.008), and employment status (p=0.028). There was no further link between other demographic factors such as gender, residency, and even exacerbation of MS between January 1, 2020 and February 1, 2022 (p>0.05). Conclusion. Although there was some hesitancy about the COVID-19 vaccination, people with MS were more likely to take the COVID-19 vaccine due to their positive attitude towards the process.